2016
DOI: 10.1111/dpr.12186
|View full text |Cite
|
Sign up to set email alerts
|

Do Aid Donors Specialize and Coordinate within Recipient Countries? The case of Malawi

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 14 publications
1
21
0
Order By: Relevance
“…Nunnenkamp et al . () find that also in later years, aid fragmentation and the overlap of donor engagement at the country and sector levels remain high; country studies support these results (e.g., Nunnenkamp et al ., ). In addition, Bulir and Hamann () have found that aid became more volatile in the late 1990s and early 2000s when the first initiatives to improve donor coordination and to increase its predictability were already underway.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Nunnenkamp et al . () find that also in later years, aid fragmentation and the overlap of donor engagement at the country and sector levels remain high; country studies support these results (e.g., Nunnenkamp et al ., ). In addition, Bulir and Hamann () have found that aid became more volatile in the late 1990s and early 2000s when the first initiatives to improve donor coordination and to increase its predictability were already underway.…”
Section: Introductionmentioning
confidence: 97%
“…Note that this is a very different issue from how to measure aid fragmentation, something that is central to the work of Nunnenkamp et al . () who do so for a single recipient, or Nunnenkamp et al . () who examine how the Paris Declaration affected fragmentation across recipients.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence at the sub-national level is limited because regional aid data are only available for a few recipient countries, mainly through the comprehensive geocoding of project-level information by the AidData initiative (Findley et al 2011). Covering Malawi's major bilateral and multilateral donors, Nunnenkamp et al (2015) do not find compelling evidence for increased aid specialization after the Paris Declaration, while the duplication of aid efforts may even have risen. Öhler (2013) -periods, 2006-2009 and 2010-2013, in order to gain at least tentative insights on whether the behavior of donors has changed recently.…”
Section: Introductionmentioning
confidence: 99%
“…At the implementation level, Klingebiel et al (2013) show that a strict application of the code of conduct should lead to a substantially enhanced sectoral DoL. This, however, does not seem to be significantly translating into reality on the ground, as Nunnenkamp et al (2015) report.…”
Section: The Political Economy Of Eu Aidmentioning
confidence: 99%